The Meaning of Spirituality in the Insan Sejahtera Concept: A Tawhidic Perspective among IIUM Students - Nor Athiah Mohd Noor; Khairul Fahmi Jamaludin; Mar'Ain Ahmad Dani; Nan Noorhidayu Megat Laksana; Nor Razinah Mohd Zain (Indonesian Journal of Islamic Education Studies (IJIES), 2026)
The International Islamic University Malaysia (IIUM) introduced the Insan Sejahtera concept to promote holistic student development by integrating spiritual, intellectual, emotional, and physical dimensions. However, limited research has examined how undergraduate students conceptualize their spiritual dimension from a Tawhidic perspective. This qualitative study explores students' understanding of spirituality within the Insan Sejahtera concept and investigates how Tawhid shapes their spiritual experiences and personal development. Data were collected through semi-structured interviews with purposively selected undergraduate students and analyzed using thematic analysis. The findings reveal that students predominantly understand spirituality as taqwa (God-consciousness), moral self-regulation, inner resilience, a source of meaning and purpose, and responsible relationships with others and the natural environment, reflecting the Tawhidic integration of Faith, ethics, and daily practice. Nevertheless, variations in students' interpretations indicate that the spiritual dimension of the Insan Sejahtera framework has not yet been consistently internalized across the university community. These findings suggest that the Insan Sejahtera concept requires a more explicit integration of Tawhid-based pedagogy to translate its philosophical foundations into students' lived spiritual experiences. This study contributes to the literature by proposing a Tawhidic interpretive model of Insan Sejahtera, demonstrating that spirituality functions not merely as an individual religious experience but as an integrative foundation that links personal transformation, ethical conduct, and holistic human development in contemporary Islamic higher education.